(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents a morphological description of the butterfly, caterpillar and pupa of Hyles euphorbiae. Hyles euphorbiae belongs to the subfamily Macroglossinae of the family Sphingidae and is distributed in natural and anthropogenic landscapes. The body of the Hyles euphorbiae larva is dark, the head capsule, chest and abdomen are reddish. Body color changes during feeding. The length of the pupa is 38-39 mm, the color is reddish-brown, and there is a pair of spiny growths at the top. The body length of Hyles euphorbiae is 46.25 mm, the forewing length is 39.54 mm and the wing length is 25.22 mm. Its wingspan was 84.5 mm. There is a dark brown border along the lower edge, base and center of the front wings. There is also a black spot on the base. The main background of the wing is yellow. The base of the hind wing is black, with a transverse dark border passing through the lower part. The main background of the hind wing is reddish.